Witt sheaves and the η‐inverted sphere spectrum. Issue 2 (7th April 2017) - Ananyevskiy, Alexey; Levine, Marc; Panin, Ivan
Abstract: Ananyevskiy has recently computed the stable operations and cooperations of rational Witt theory. These computations enable us to show a motivic analog of Serre's finiteness result. Theorem: Let k be a field of characteristic different from two. Then π n A 1 ( S k − ) ∗ is torsion for n > 0 . As an application, we define a category of Witt motives and show that rationally this category is equivalent to the minus part of SH ( k ) Q .